(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess patients’ knowledge and adherence to preventive measures for recurrent upper urinary tract stones (recurrent kidney and/or ureteral stones) and to analyze related factors. Methods: A cross-sectional descriptive-analytic study was conducted on 189 patients with recurrent upper urinary tract stones at the Outpatient Department, 108 Military Central Hospital, from December 2025 to April 2026. Sample size was estimated using the formula for a single proportion, and consecutive convenience sampling was applied. Data were collected using structured questionnaires and analyzed with SPSS 26.0. Results: Only 18.0% of patients demonstrated good knowledge of preventive measures, and 25.4% correctly identified the recommended daily fluid intake. Adherence to physician instructions was relatively high (87.3%), and 74.6% reported taking medication as prescribed. However, only 19.6% of patients consumed at least 2 liters of water per day. Risk behaviors remained common, including occasional consumption of harmful beverages (49.2%) and self-medication when experiencing pain (31.7%). The most commonly reported barriers to adherence were forgetfulness (73.0%) and lack of time (24.3%). Knowledge level was significantly associated with the adoption of preventive measures (p = 0.018). No statistically significant association was observed between overall adherence level and recurrence frequency or recurrence interval (p > 0.05). Conclusions: Patients demonstrated limited knowledge and adherence regarding preventive measures for recurrent upper urinary tract stones, particularly in lifestyle modification and adequate daily water intake. Better knowledge was associated with improved preventive practices. These findings highlight the importance of health education and individualized counseling to reduce the risk of stone recurrence.